Plant eIF4E isoforms as factors of susceptibility and resistance to potyviruses - Zlobin, Nikolay; Taranov, Vasiliy (Frontiers in Plant Science, 2023)
Potyviruses are the largest group of plant-infecting RNA viruses that affect a wide range of crop plants. Plant resistance genes against potyviruses are often recessive and encode translation initiation factors eIF4E. The inability of potyviruses to use plant eIF4E factors leads to the development of resistance through a loss-of-susceptibility mechanism. Plants have a small family of eIF4E genes that encode several isoforms with distinct but overlapping functions in cell metabolism. Potyviruses use distinct eIF4E isoforms as susceptibility factors in different plants. The role of different members of the plant eIF4E family in the interaction with a given potyvirus could differ drastically. An interplay exists between different members of the eIF4E family in the context of plant–potyvirus interactions, allowing different eIF4E isoforms to modulate each other’s availability as susceptibility factors for the virus. In this review, possible molecular mechanisms underlying this interaction are discussed, and approaches to identify the eIF4E isoform that plays a major role in the plant–potyvirus interaction are suggested. The final section of the review discusses how knowledge about the interaction between different eIF4E isoforms can be used to develop plants with durable resistance to potyviruses.